Structural Change, Labor Market and Employment in Brazil after the 2017 Labor Market Reform - Araújo, Eliane; Galete, Rinaldo; Caldarelli, Carlos Eduardo (Panoeconomicus, 2023)
The objective of this study is to analyze the effects of the set of measures adopted by the labor reform of 2017 on the generation of employment and income in Brazil. The study is based on the literature that highlights the importance of structural change in employment as a key element for economic growth and development, emphasizing that in Brazil, there is still a view that the labor market should take on more flexible work relationships to advance in the improvement of jobs, levels of employment, productivity and income. Subsequently, the article summarizes and critically comments on the main measures of the labor law reforms adopted in post-2017 Brazil. Finally, it presents an analysis of the behavior of the labor market in Brazil between 2012 and 2022 based on data from the PNADC/IBGE survey. The main results of the survey confirm that the labor reform of 2017 has not shown advances in labor market indicators or in the main macroeconomic aggregates of the country. In contrast, the data suggest deterioration in the indicators of employment, income and allocation of workers in occupations with low productivity and income characteristics.JEL: J08, J83, O11, O43.